Sociodemographic and entomological factors associated with dengue outbreaks in Sabah - Kunasagran, Priya Dharishini; Syed Abdul Rahim, Syed Sharizman; Jeffree, Mohammad Saffree; Atil, Azman; Hidrus, Aizuddin; Madrim, Mohd Faizal; Muyou, Adora J.; Goh, Gary Chun Chao; Nasib, Rudi; Mohammad, Ahmad Hazim; Dapari, Rahmat; Hassan, Mohd Rohaizat; et al. (Universiti Putra Malaysia, 2023)
Introduction: Dengue fever has reached an endemic status in approximately 128 countries worldwide, with a significant rise in the frequency of outbreaks. In recent years, Sabah has witnessed a surge in dengue cases, accompanied by a corresponding increase in dengue mortality. The reported deaths rose from 8 in 2017 to 29 in 2018, marking a significant 362% increase within a year. This study aimed to investigate factors associated with dengue outbreaks in Sabah. Methods: A cross-sectional study was conducted using the surveillance data from 2017 to 2020 available in e-Dengue, the Malaysian National Dengue Registry. A simple and multivariate logistic regression was performed to determine the association between factors and the dengue outbreak. Results: Aged 21–59 have 66 % lower risk odds than 0–12 years old in contributing to dengue outbreaks (95% CI: 0.272–0.406). There are 1.729 times increased risk in students than in unemployed personnel of contributing to dengue outbreaks (95 % CI: 1.565–1.910), with employed personnel having 20.7% lower odds than unemployed personnel of contributing to dengue outbreaks (95 % CI: 0.623–0.767). Urban localities have 44.9% higher odds of developing dengue outbreaks than rural localities (OR: 1.449, 95 % CI: 1.334–1.574). AI ≥ 1% has 78.2% higher odds than AI <1% with a dengue outbreak (95 %: CI: 1.642–1.933). Conclusion: Future dengue prevention and control initiatives in Sabah may benefit greatly from this study’s sociodemographic and entomological findings.